2012
DOI: 10.1111/j.1600-0706.2012.20319.x
|View full text |Cite
|
Sign up to set email alerts
|

Size‐selective fishing affects sex ratios and the opportunity for sexual selection in Alaskan sockeye salmonOncorhynchus nerka

Abstract: Selective exploitation can cause adverse ecological and evolutionary changes in wild populations and also affect sex ratios but few studies have empirically documented skewed sex ratios in exploited fishes (other than species with extreme sexual size dimorphism, SSD). To investigate the possibility of sex‐selective fishing on Alaskan sockeye salmon Oncorhynchus nerka, we assessed sex ratios in fish at two spatial scales: within each of five fishing districts and among 13 breeding populations in one of these di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 52 publications
0
46
0
Order By: Relevance
“…The sex ratio is important for the propagation of a fish species because sex imbalances produce changes in competitive behavior at the spawning grounds and affect mate choice, which can subsequently result in evolutionary pressure and changes in the ecological structure (Kendall and Quinn, 2013). Limited studies have analyzed the sex ratio of the small yellow croaker; in this study, the sex ratio from the fish caught in the single-stick stow nets was less than 1 and showed a tendency to increase over the decade.…”
Section: Sex Ratio Variationmentioning
confidence: 94%
“…The sex ratio is important for the propagation of a fish species because sex imbalances produce changes in competitive behavior at the spawning grounds and affect mate choice, which can subsequently result in evolutionary pressure and changes in the ecological structure (Kendall and Quinn, 2013). Limited studies have analyzed the sex ratio of the small yellow croaker; in this study, the sex ratio from the fish caught in the single-stick stow nets was less than 1 and showed a tendency to increase over the decade.…”
Section: Sex Ratio Variationmentioning
confidence: 94%
“…However, the sex composition of the fishery catch is influenced by a combination of the following factors: (1) differences in the size-, age-, and sex-specific retention selectivity imposed by the minimum retention size (MRS) in each fishery (Kendall and Quinn 2013); (2) the size-, age-, and sexspecific vulnerability of fish resulting from their interaction with the fishing gears (Ryer 2008;Somerton et al 2011) and/or their availability to the fishing gears (Okamura et al 2014;Sampson 2014); and (3) the spatial-, temporal-, and sex-specific growth rates of the fish that are retained by the different sampling gears (Poole 1961;Planes et al 1999;Wilderbuer and Turnock 2009). For instance, different MRS limits are implemented in the recreational and commercial Summer Flounder fisheries (NEFSC 2013), and some limited evidence suggests that at a given length, males' and females' availability or vulnerability to fishing effort may vary seasonally and between the recreational fishery and the NMFS-NEFSC survey (Morson et al 2012).…”
mentioning
confidence: 99%
“…Size-selective fishing can alter the sex ratio of a population (Kendall and Quinn 2013) and can influence the reproductive potential of the stock (Rowe and Hutchings 2003;Claereboudt et al 2004;Rijnsdorp et al 2010), and genetic traits that are selected against by implementing an MRS as a management strategy may be difficult to recover (Enberg et al 2009). …”
mentioning
confidence: 99%
“…The sex ratio (female to male) of small yellow croaker in the catch composition depended on the selectivity of the fishing gear (Xiong et al, 2016). Kendall and Quinn (2013) reported that there were significantly higher catch rates for male Alaskan sockeye salmon Oncorhynchus nerka than for females over six decades, and revealed that skewed sex ratios may change intra-sexual competition and behavior characteristics of mate choice on the breeding grounds, altering the demographic and evolutionary pressures on fish. A similar viewpoint, that sexual selection likely caused greater fishery-induced evolution toward small individuals was favored by both Hutchings and Rowe (2008) and Urbach and Cotton (2008).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the impacts of heavy fishing on fishery resources and the ecosystem have become increasingly serious; the population genetic characteristics of several species have significantly changed, and life-history tactics have been altered (Hauser, Adcock, Smith, Ramirez, & Carvalho, 2002;Yang et al, 2015;Thériault, Dunlop, Dieckmann, Bernatchez, & Dodson, 2008;Sharpe & Hendry, 2009). Gillnet-selective has caused adverse ecological and evolutionary changes in wild populations and has also affected sex ratios; this is particularly apparent in commercially and biologically important species (Sbrana, Belcari, Ranieri, Sartor, & Viva, 2007;Kendall, Hard, & Quinn, 2009;, 2013 These assessment approaches require information on population structure and selectivity to determine the impact of fishery on the population.…”
Section: Introductionmentioning
confidence: 99%